THE EFFECT OF INTRA-AORTIC BALLOON PUMP IN PATIENTS WITH LOW EJECTION FRACTION UNDERGOING CORONARY ARTERY BYPASS GRAFTING - KHAN, T; ASHRAF, T; ROOMI, F (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess risk factors that predict the length of stay and 30-day mortality in subjects undergoing CAGB to evaluate the impact of IABP support in patients with low ejection fraction. The prospective study was conducted in the Cardiology Department of Punjab Institute of Cardiology Lahore from January 2022 to January 2023. A total of 315 patients were included in the study. The sample was divided into a study group (n=110, having LVEF ≤ 30%) and a control group (n=205, having EF > 30%). Pre-operative and intraoperative data of the patients were recorded. Post-operative complications were recorded, including LOS in the hospital and 30-day mortality. Patients in the study group required more emergency CABG ( P = .005), and IABP was also used more frequently in patients having EF< 30% (P<.001). LOS in hospital (P<.001) and ICU (P<.001) and 30-day mortality (P=.009) were higher in the study group. According to multivariate logistic regression analysis, in the study group history of cerebrovascular disease ( P = .018), peripheral vascular disease ( P = .004), congestive heart failure ( P = .027), and IABP use ( P = .002) were associated with the rate of 30-day mortality. Moreover, the increased length of hospital stay in these patients was associated with an increase in age (P<.001), hypertension (P=.040), and IABP use (P=.009). Based on the results, it can be concluded that the low ejection fraction positively affects increased LOS and 30-day mortality in subjects undergoing CABG; IABP insertion is a significant predictor of increased LOS and 30-day mortality and increases post-operative complications.